SOCCER: MOST FAVORITE CASUAL GAME - Setyabudi, Djoko; Dewi, Reni Shinta; Pradhanawati, Ari (Master of Communication Science Program, Universitas Diponegoro, 2024)
This study aims to discover the favorite casual games in adults, both gamers and not. Respondents ranged in age from 17 to 56.This study fills the research gap about the taste of casual gaming in the city of Semarang, because so far researchers have often found many studies on the types of games that fall into the category of ‘heavy games’ and tend to be played by game addicts who dedicate time and money to playing games or e-sports athletes. This research gives us information about the types of casual games that are most liked by adult game players in the city of Semarang. Meanwhile, the casual game category is ignored because it is only played by players who are not serious and just to pass the time. In addition, it also provides information on the extent to which casual players are willing to play the type of games that they think are worth playing, including the criteria for games to be installed to try to play. Inside their smartphones are installed Android-based game applications that are played. Conducted in Semarang, the sampling technique used was convenience sampling with 170 people. The data will be analyzed with quantitative descriptive methods to describe the condition of the sample. The findings showed that respondents liked games that were lightweight, uncomplicated, and required high concentration. Games that can be played in the past and tend to be dexterous.